Pengaturan Pajak Pertambahan Nilai dan Pajak Penghasilan Atas Barang Dalam Transaksi Perdagangan Dengan Sistem Elektronik (E-Commerce) - Ni Luh Debby Srinitha Mulyani; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Fakultas Hukum Universitas Warmadewa, 2025)
Online buying and selling transactions can cause issues in the tax collection system similar to those in conventional buying and selling. The policies for income tax (PPH) and value-added tax (PPN) between conventional trade systems and e-commerce are similar. The object of income tax in e-commerce transactions is what is received by the taxpayer from the increase in economic capacity, while the object of value-added tax in e-commerce transactions includes the provision of taxable goods that are sold, the use of taxable goods, taxable services, and the export of taxable goods. The research problem formulation of this study is (1) How is the taxation of objects that can be subjected to income tax (PPH) and value-added tax (PPN) in e-commerce transactions? and (2) What is the procedure for imposing income tax (PPH) and value-added tax (PPN) on goods that are transacted electronically (e-commerce)? The research method taken is based on normative legal research, and the approaches used are legislative and conceptual approaches. The goal of this research is to understand the regulation of value-added tax as well as income tax on goods in transactions conducted through internet utilization, as well as the procedure for imposing value-added tax and income tax on electronically transacted goods (e-commerce).